MEMBANGUN KESADARAN ETIS DENGAN BERKATA JUJUR PADA SISWA SMA SEKOLAH X - Matthew Stanislaus; Raja Oloan Tumanggor; Ben Kristofer Benedict (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Dishonest behavior, such as lying and cheating, is still commonly found among adolescents in school settings. This reflects a lack of ethical awareness among students, where the motivation to be honest is generally still driven by external factors, such as fear of punishment or the desire to be viewed favorably by peers. This program aims to test the effectiveness of the psychoeducational program “Building Ethical Awareness Through Honesty” in enhancing understanding and the internalization of the value of honesty among middle-aged adolescents. Using a cognitive and social psychology approach through Lawrence Kohlberg’s theory of moral development and Albert Bandura’s social learning theory, this program is designed to map the factors that support honest behavior and the factors that trigger dishonesty using examples that are easy to understand. This psychoeducational program was implemented with 37 students in a vocational psychology class at Private School X. The results of this program demonstrate that school-based psychological interventions can have a positive impact on fostering students’ moral awareness. Through a contextual approach, this program successfully broadened students’ perspectives and fostered the internalization of values. The behavior of speaking honestly that emerged after the activities was no longer driven by external pressure but arose independently from the students’ self-awareness as learners. Participants gave very positive feedback and expressed hope that this character-building program could continue to be implemented on an ongoing basis.